The Definition and Diagnosis of Developmental Prosopagnosia. Issue 2 (February 2017) - Bate, Sarah; Tree, Jeremy J.
Over the last 20 years much attention in the field of face recognition has been directed towards the study of developmental prosopagnosia (DP), with some authors investigating the behavioural characteristics of the condition, and many others using these individuals to further our theoretical understanding of the typical face-processing system. It is broadly agreed that the term "DP" refers to people who have failed to develop the ability to recognize faces in the absence of neurological illness or injury, yet more precise terminology in relation to potential subtypes of the population are yet to be confirmed. Furthermore, specific diagnostic techniques and inclusion and exclusion criteria have yet to be uniformly accepted across the field, making cross-paper comparisons and meta-analyses very difficult. This paper presents an overview of the current challenges that face research into DP and introduces a series of papers that attempt to further our understanding of the condition's characteristics. It is hoped that this special issue will provide a springboard for further research addressing these issues, improving the current state of the art by ensuring the quality of theoretical investigations into DP, and by posing advances that will assist those who have the condition.